Factors associated with gingival enlargement among patients undergoing orthodontic treatment at the University of the Philippines Manila Graduate Program in Orthodontics - Gamboa, Gianina Camille S.; Mandigma, Ma. Karina E.; Ranches. Maria Karla F. (Co-author).
In a study by Gursoy in 2007, a 46.4% prevelance of gingival enlargement among patients using fixed orthodontic appliances was reported. Gingival enlargement complicates the patient's plaque control. This could lead to periodontal breakdown and subsequent development of periodontal disease. This study aims to describe the prevalence of gingival enlargement among orthodontic patients being treated at the University of the Philippines Manila Graduate Program in Orthodontics. METHODS: A total of 40 participants were included in this study. Guided interviews were conducted by the researchers to obtain personal information and the participants' medical history. This was followed by an intraoral examination in order to detect the presence or absence of gingival enlargement. An intraoral photograph was taken if gingival enlargement was present. The patient was the asked to swish diluted disclosing solution for 30 seconds. After which, the patient's plaque index was recorded using the Turesky Modification of Quigley and Hein Plaque Index.RESULTS: The overall prevalence of gingival enlargement among the participants was 57.50% being relatively higher in females, students and younger age groups. All the subjects in the first phase of orthodontic treatment and those with a diagnosis of Skeletal Class II Dental Class I, Skeletal Class I Dental Class II, Skeletal Class III Dental Class I showed a 100% prevalence for gingival enlargement. In patients who are using NiTi wires, a higher prevalence of gingival enlargement has been observed as compared top those who use stainless wires. However, there were no statistical significances between all the factors studied except for plaque index which had a p-value of 0.0119. CONCLUSION: Plaque index is the only factor observed to have a significant association with gingival enlargement.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.